2008
DOI: 10.1103/physrevlett.101.218301
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Shear Profile Measurements in Entangled Polymers

Abstract: We use confocal microscopy and particle image velocimetry to visualize motion of 250-300 nm. fluorescent tracer particles in entangled polymers subject to a rectilinear shear flow. Our results show linear velocity profiles in polymer solutions spanning a wide range of molecular weights and number of entanglements (8 Z 56), but reveal large differences between the imposed and measured shear rates. These findings disagree with recent reports that shear banding is a characteristic flow response of entangled polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 33 publications
(41 reference statements)
5
40
0
Order By: Relevance
“…These arguments were shown correct in very recent simulations [152]. Since 2006, strong efforts have been made to provide a 1D picture using velocimetry techniques in various flow geometries, mostly CP [87,126] and parallel plates [17,74] and marginally TC [78] and pipe [151]. During the past decade, extensive sets of particle tracking velocimetry (PTV) experiments combined with global rheology by Wang's group [146] showed that shear banding can emerge in polymer solutions and melts (Figure 3a).…”
Section: B Shear Banding In Polymers Solutions and Meltsmentioning
confidence: 92%
“…These arguments were shown correct in very recent simulations [152]. Since 2006, strong efforts have been made to provide a 1D picture using velocimetry techniques in various flow geometries, mostly CP [87,126] and parallel plates [17,74] and marginally TC [78] and pipe [151]. During the past decade, extensive sets of particle tracking velocimetry (PTV) experiments combined with global rheology by Wang's group [146] showed that shear banding can emerge in polymer solutions and melts (Figure 3a).…”
Section: B Shear Banding In Polymers Solutions and Meltsmentioning
confidence: 92%
“…1 On the other hand, in recent experimental work with entangled synthetic polymers shear banding was not observed, but instead interfacial slip was suggested as the origin of strain loss. 10,11 Gradient banding has also been found in glassy starlike polymers. [12][13][14] Here, depending on the functionality and arm length of the star polymers, banding may be related to entanglements and/or to excluded volume interactions.…”
Section: Introductionmentioning
confidence: 95%
“…A well-known failure of the DE theory lies in its inability to predict the experimentally observed monotonic steady state constitutive relationship between shear stress and shear rate [Doi and Edwards (1979)]. Specifically, if the constitutive curve indeed is non-monotonic as predicted by the DE model, shear banding should occur, meaning that bands with different shear rates could form in the sample above a critical shear stress or shear rate; however, this non-monotonicity or shear banding has not been normally observed [Hu (2010); Hayes et al (2008)]. On the other hand, in step strain tests, it was found that the DE model underestimates the strain softening behavior in some cases [Osaki and Kurata (1980); Vrentas and Graessley (1982)].…”
Section: Introductionmentioning
confidence: 99%